(untitled) (Journal of Asian Development Studies, 2024)
This research article delves into the intricate interplay between criminality and human rights violations within legal frameworks. This research scrutinizes how criminal acts, ranging from petty offenses to egregious crimes, cast a pervasive shadow over the landscape of justice and individual liberties.This article illuminates the multifaceted ways criminal behavior intersects with fundamental human rights principles by examining case studies, legislative measures, and international conventions. It explores the challenges posed by balancing the imperatives of law enforcement with the protection of civil liberties, emphasizing the need for nuanced approaches that safeguard human dignity amidst the pursuit of justice. Additionally, the article investigates the role of legal systems in addressing systemic injustices and promoting accountability for human rights violations perpetrated through criminal means. Through a comprehensive analysis, this study seeks to contribute to scholarly discourse on the complex dynamics between criminality, justice, and human rights, ultimately advocating for policies and practices that uphold the rights and dignity of all individuals within the realm of law